$\esthree{-x + 3 y + z z = 2}{\fraction{1}{2} x - \fraction{3}{2} y - z = -1}{-\fraction{1}{3} x + y + \fraction{2}{3} z = \fraction{2}{3}} $

Solve for x, y, z

x=3y-2\text{, }y\in \mathrm{R}\text{, }z=0

x=3y+2\text{, }y\in \mathrm{R}\text{, }z=2

## Share

Copied to clipboard

## Examples

Quadratic equation

{ x } ^ { 2 } - 4 x - 5 = 0

Trigonometry

4 \sin \theta \cos \theta = 2 \sin \theta

Linear equation

y = 3x + 4

Arithmetic

699 * 533

Matrix

\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]

Simultaneous equation

\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.

Differentiation

\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }

Integration

\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x

Limits

\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}